Product study of the reactions of γ-caprolactone and γ-heptalactone initiated by OH radicals at 298 K and atmospheric pressure: Formation of acyl peroxynitrates (APN). (May 2023) - Baptista, Andrea; Gibilisco, Rodrigo G.; Patroescu-Klotz, Iulia; Illmann, Niklas; Wiesen, Peter; Blanco, María B.; Teruel, Mariano A.
Abstract: A product study was performed for the reaction of γ-caprolactone (GCL) and γ-heptalactone (GHL) initiated by OH radicals at (298 ± 2) K and atmospheric pressure, in presence of NOx . The identification and quantification of the products were performed in a glass reactor coupled with in situ FT-IR spectroscopy. The following products were identified and quantified with the corresponding formation yields (in %) for the OH + GCL reaction: peroxy propionyl nitrate (PPN) (52 ± 3), peroxy acetyl nitrate (PAN) (25 ± 1), and succinic anhydride (48 ± 2). For the GHL + OH reaction, the products detected with their corresponding formation yields (in %) were the following: peroxy n-butyryl nitrate (PnBN) (56 ± 2), peroxy propionyl nitrate (PPN) (30 ± 1) and succinic anhydride and (35 ± 1). Upon these results, an oxidation mechanism is postulated for the title reactions. The positions with the highest H-abstraction probabilities for both lactones are analyzed. Specifically, the increased reactivity of the C5 site, as indicated by structure reactivity estimations (SAR), is suggested by the identified products. For both GCL and GHL degradation appears to follow degradation paths including ring preservation and opening. The atmospheric implications of the APN formation as a photochemical pollutant and as NOx reservoirs of species is assessed. Graphical abstract: Image 1 Highlights: First products yields study of 5-membered lactones atmospheric degradation. Gamma-lactones degradation by OH leads to ring opening and/or oxidation. Significant peroxy nitrates formation in presence of NO2 (polluted areas). Evidence of alkyl and acetyl peroxy radicals in the lactones + OH reaction. APN as NOx reservoirs in the atmospheric reactions of cyclic esters.